Ekolirik Dalam Lagu Anak Jepang: Tinjauan Dua Douyou - Mhd. Pujiono; Abdul Gapur (Universitas Diponegoro, 2019)
[Ecolyrics in Japanese Children Songs: A Review of Two Douyou] This paper is an ecolinguistic analysis of the lyrics of two douyou (Japanese children songs) – coined in this paper as ‘eco-lyrics’. The aim was to analyse the representation of the state of the natural environment and the hometown in the lyrics of Japanese children's songs and the value that Japanese society inculcates to their children in relation to the natural environment. The two songs chosen were furusato and kokyou no sora. As a qualitative-descriptive study, this paper focuses on the intertextual discussion using the coherence approach of Ramlan (1993) and the semantic product of Burnett (2003). The result are a representation of the natural environment for the Japanese society in two douyou consisting of a thick traditionality, a place of longing, a place where family and friends live, a place to return home, a place that is beautiful and blends with nature, a comfortable and beautiful place. Then the values embedded in his children consist of emotional semantics, empirical semantics, origin semantics, contextual semantics, and functional semantics. <a href=